DOI: 10.35376/10324/15014
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la participación y esencia de la familia en la empresa: un análisis en la empresa familiar desde el enfoque de capacidades dinámicas

Abstract: 'Family firms are important, not only because they make an essential contribution to the economy, but also because of the long-term stability they bring, the specific commitment they show to local communities, the responsibility they feel as owners and the values they stand for. These are precious factors against the backdrop of the current financial crises'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 262 publications
(1,099 reference statements)
0
1
0
Order By: Relevance
“…While some studies confirmed the existence of class bias (Contreras and Morales 2015; Mackenna 2015), others suggested that there was no consistent relationship (Ramírez 2015), that it was negative (Bargsted et al 2015), or that it was conditional on district size (Brieba 2015). All these studies used district-level data, except for Mackenna 2015, which used individual-level survey data, and Contreras and Morales 2015, which used both. It is probably not a coincidence that precisely these last two studies found positive class bias while most others did not.…”
Section: The Chilean Reformmentioning
confidence: 99%
“…While some studies confirmed the existence of class bias (Contreras and Morales 2015; Mackenna 2015), others suggested that there was no consistent relationship (Ramírez 2015), that it was negative (Bargsted et al 2015), or that it was conditional on district size (Brieba 2015). All these studies used district-level data, except for Mackenna 2015, which used individual-level survey data, and Contreras and Morales 2015, which used both. It is probably not a coincidence that precisely these last two studies found positive class bias while most others did not.…”
Section: The Chilean Reformmentioning
confidence: 99%